Topological localization of a segment of the eel voltage-dependent sodium channel primary sequence (AA 927-938) that discriminates between models of tertiary structure - Gordon, RD (J Neurosci, 1988)
Antibodies were raised against a synthetic peptide corresponding to residues 927–938 of the eel electroplax sodium channel primary sequence. This segment, lying between putative internal repeat domains II and III, is postulated to be exposed on the cytoplasmic surface of the membrane in several recent models of channel tertiary structure and on the external surface in another. The antiserum and affinity-purified IgG derived from it specifically recognize the peptide and the eel sodium channel in a solid-phase radioimmunoassay and bind to a single diffuse band of 260–280 kDa on Western blots of eel electroplax membrane proteins. All reactions are blocked by co-incubation of the antibodies with the synthetic peptide (1 microM). The antibody immunoprecipitates the solubilized channel in a form that retains its characteristic high-affinity binding of saxitoxin. In eel electroplax, the antibodies label only the innervated membrane known to contain sodium channels; at the ultrastructural level, this labeling is exclusively associated with the cytoplasmic surface of the membrane. Sodium channels containing the epitope are not seen in the postsynaptic membrane or in the membrane of the presynaptic nerve terminal. Segment 927–938 of the eel sodium channel is accessible on the surface of the protein in its solubilized form and is exposed in the cytoplasmic face of the innervated membrane of the electroplax in situ. This location is consistent with 3 models of channel structure but not with a fourth.